The Role of Gut Microbiota in Insomnia: A Systematic Review of Case–Control Studies - Yun Wang; Suyi Xie; Sizhe Chen; Chenyu Li; Yeuk Lam Chan; Ngan Yin Chan; Yun Kwok Wing; Francis K. L. Chan; Qi Su; Siew C. Ng (Life)
Background: Insomnia is one of the most prevalent health concerns and has a major impact on human health and quality of life. Increasing evidence indicates the gut microbiota’s role in sleep regulation through the gut–brain axis. This systematic review aims to summarise current evidence on the role of gut microbiota alterations in insomnia. Methods: We searched PubMed, Embase, and Cochrane Library through November 2024 for case–control studies comparing gut microbiota in insomnia subjects and controls. The primary outcome was changes in microbiota diversity and bacteria taxonomy. Results: We included 15 case–control studies from 14 articles, consisting of 1321 subjects (603 insomnia; 718 controls). Eight studies showed reduced alpha diversity and eleven showed altered beta diversity in insomnia subjects. Depletions of specific taxa such as Lactobacillales (class Bacilli), Faecalibacterium, and Lachnospira and the enrichment of Actinobacteria, Bacteroidales (class Bacteroidia), and several genera, including Streptococcus, Blautia, Lactobacillus, Clostridium, Holdemanella, and Eubacterium hallii, were observed in insomnia subjects. There was a negative association between insomnia severity and abundance of Faecalibacterium and Lachnospira, and positive associations with Blautia. Conclusions: This systematic review identifies specific alterations in gut microbiota among insomnia subjects characterised by taxonomic changes that may serve as promising therapeutic targets for sleep disorders.